ANALISIS PENGGUNAAN MODEL ALTMAN Z-SCORE, MODEL SPRINGATE, MODEL GROVER, DAN MODEL ZMIJEWSKI SEBAGAI PREDIKTOR KEBANGKRUTAN - Klemens Bonifasius Tiono; Fredella Colline (Jurnal Akuntansi, 2020)
The purpose of this research to know: (1), to find out which firm is predicted being bankruptcy according to the Altman Z-score model, Springate model, Grover model and Zmijewski model, (2) to find out wether there is difference between the fourth model of bankruptcy prediction (3) to find out which model have highest level accuration to predict bankcruptcy of the oil and gas firm. After the oil and gas firm was analyzed with the fourth model of bankruptcy prediction, the result is (1) according the altman Z-score model there is 5 firm that predicted have potential to being bankruptcy and only 1 firm have a healthy financial condition (2) according the Springate model there is 5 firm that predicted have potential to being bankruptcy and 2 firm have a healthy financial condition, (3) according the Grover model there is 2 firm that predicted have potential to being bankruptcy and 5 furm have a healthy financial condition, (4) according the altman Zmijewski model there is 1 firm that predicted have potential to being bankruptcy and 6 furm have a healthy financial condition. According to the result of Kruskal Wallis Test using IBM SPSS 24 that Altman Z-score model with Springate model and Grover model with Zmijewski model have same average score result. The most accurate level achived by Springate model. Keywords : bankruptcy, financial distress, altman z-score model, springate model, grover model, zmijewski model